Principals' Management of Co-curricular Activities as Determinant of Students' Completion Rates in Public Technical Training Institutions in Kiambu County, Kenya - Mwaura, Mercy; Waweru, Samuel; Mbirithi, Daniel (African Journal of Education and Practice, 2023)
Purpose: Principals play an important role in the management of co-curricular activities such as planning. However, in Kiambu County, students' completion rates in technical training institutions are low. This study intended to assess principals' management of co-curricular activities as determinant of students' completion rates in public technical training institutions in Kiambu County, Kenya. Methodology: The study adopted mixed methodology and concurrent triangulation research design. Qualitative data were analyzed thematically along the objectives and presented in narrative forms. Quantitative data were analyzed using descriptive statistics such as frequencies and percentages and inferentially using Pearson's Product Moment Correlation Analysis with the help of Statistical Packages for Social Sciences and presented by using tables. Findings: The study established that, dropout rates among students in public technical training institutions have been high which has led to fluctuating students' completion rates. The study further established that principals play a key role in the management of co-curricular activities and how such activities influence students' completion rates in public technical training institutions. However, the study revealed that most principals are rarely involved in the actual planning of CCAs but appreciate the value of such activities in the wholistic growth and development of students. Unique Contribution to Theory, Practice and Policy: The study recommends that, as a practice, principals should continue allocating more resources for improving infrastructure for co-curricular activities. As a policy, the Ministry of Education should formulate a policy enabling colleges to partner with other statehooders to provide resources and better the quality of facilities meant for CCAs in technical training institutions.